KUALITAS AIR BENDUNGAN SUNGAI BADUNG DAN KOLAM PANCING “X” - Dewa Ayu Wahyunia Ratna Dewi; Deny Suhernawan Yusup; Ngurah Intan Wiratmini (Program Studi Biologi Universitas Udayana, 2025)
The water quality in the northern coastal area of ​​Serangan Island, Denpasar, which receives flow from many large (Tukad) and small (loloan) rivers is indicated to have experienced organic and inorganic pollution including heavy metals. The Badung River Dam and fishing pond